A business needs-based planning methodology for information systems in the firm. (1st January 2001) - Rubenstein, Albert H.; Geisler, Eliezer; Hoffman, Gerald
This paper presents a methodology for linking planning and strategy for Information Systems in the firm with the Goals of the firm and its Critical Success Factors in its lines of business. The approach starts with the effects of business and economic conditions within which the firm is operating and is likely to operate in the future. From the firm's goals and these limiting conditions, it leads the management through identification of the needs for IT capabilities and services to the various businesses and supporting functions. The management or users of IT then identify their needs and the changes in their needs for IT. These needs are then addressed by the managers of IS in terms of how they can meet their users' needs. Finally, a coherent IT strategy is developed from the above steps, showing the linkage between needs and IS strategies. Two case studies from our consulting practice are presented, along with metrics for the results of the strategies.